1988
DOI: 10.1016/0735-1097(88)90376-2
|View full text |Cite
|
Sign up to set email alerts
|

The xanthine oxidase inhibitor oxypurinol does not limit infarct size in a canine model of 40 minutes of ischemia with reperfusion

Abstract: Free radicals such as superoxide (.O2-) produced by xanthine oxidase might cause cell death during reperfusion after myocardial ischemia. The effect of the xanthine oxidase inhibitor allopurinol on infarct size in ischemia-reperfusion models has been variable, possibly because of differences in treatment duration. Adequate inhibition of xanthine oxidase may require a sufficient pretreatment period to permit conversion of allopurinol to oxypurinol, the actual inhibitor of superoxide production. To test more def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…First, it is possible that in the presence of a treatment, tetrazolium used early after reperfusion may artifactually stain tissue that is irreversibly injured; this artifact would not be observed when tetrazolium is used after longer periods of reperfusion21,23,25,26 or when infarct size is assessed histologically. 20,22,24 Another possibility is that treatments only delay free radical-induced cell death and that the initially salvaged tissue undergoes necrosis later in the reperfusion phase ("delayed reperfusion injury"). Such a mechanism could occur if free radical production continued after drug levels decreased below their therapeutic levels.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is possible that in the presence of a treatment, tetrazolium used early after reperfusion may artifactually stain tissue that is irreversibly injured; this artifact would not be observed when tetrazolium is used after longer periods of reperfusion21,23,25,26 or when infarct size is assessed histologically. 20,22,24 Another possibility is that treatments only delay free radical-induced cell death and that the initially salvaged tissue undergoes necrosis later in the reperfusion phase ("delayed reperfusion injury"). Such a mechanism could occur if free radical production continued after drug levels decreased below their therapeutic levels.…”
Section: Discussionmentioning
confidence: 99%
“…The continuation of iloprost therapy until 48 hours after reperfusion did limit the extent of injury assessed 72 hours after reperfusion.33 Thus, it is not surprising that administration of oxypurinol before reperfusion failed to limit the ultimate extent of myocardial injury in dogs subjected to 40 or 90 minutes of coronary artery occlusion followed by reperfusion for 1 or 4 days. [34][35][36] Histochemical reagents such as triphenyltetrazolium chloride and nitro blue tetrazolium impart pigmentation to myocardium that retains the activities of dehydrogenase enzymes and their coenzymes,37 which may not be synonymous with cell viability. Nevertheless, the calculation of the extent of myocardial infarction using triphenyltetrazolium chloride or nitro blue tetrazolium correlates with the assessment of infarct size by electron microscopy,37 histopathology,38,39 the depletion of creatine kinase activity,40 the uptake of infarct-avid radionuclides,41,42 or antimyosin antibodies.43 According to Kloner et al,44 electron microscopic analysis of myocardium confirmed that triphenyltetrazolium chloride "... can reliably identify those areas of myocardium that demonstrate severe ultrastructural damage during the early phases of myocardial infarction, prior to the development of frank necrosis on histologic examination."…”
Section: Histological Examinationmentioning
confidence: 99%
“…Indeed, when reperfusion is performed rapidly, the protective capability of the scavenger agent may be overwhelmed by the very rapid generation of free radicals (30). Many studies that have shown protective effects have used a slow reperfusion procedure (21,28,49,50), whereas many of the negative studies used a rapid reperfusion protocol (10,13,24,26,34,39,40,41,48). The present study cannot definitively answer the question of whether slow reperfusion is desirable or not.…”
Section: Revascularization Proceduresmentioning
confidence: 74%
“…supero• dismutase and catalase, and of various agents interfering with their metabolic sources, such as allopurinol to block the xanthine o• pathway, have been evaluated. The protective effects observed in some studies with various animal species (1, 2,4,20,21,32,33,37,50,51) could not, however, bc rcproduced in others (10,13,24,26,34,39,40,41,48). Considering these discrepancies, the usefulness of the therapeutic approach is questionable and, consequently, so is the role played by oxygen radicals in the etiology of reperfusion damage (9).…”
Section: Introductionmentioning
confidence: 99%